Star formation rates for elliptical galaxies derived from the WISE 12- and 22- µm emission - Nur Hidayah Mohd Ali,; Zamri Zainal Abidin,; Hwang, Chorng-Yuan (Penerbit Universiti Kebangsaan Malaysia, 2022)
We investigated the star formation rates (SFRs) of selected elliptical galaxies using the infrared data from the Wide-field Infrared Survey Explorer (WISE). The elliptical galaxies were selected from the Sloan Digital Sky Survey (SDSS) MPA-JHU catalog and morphology classified by Galaxy Zoo catalog. We used the 3.4-µm emission (W1) of WISE to represent the stellar mass of the galaxies and the 12- and 22-µm emission (W3 and W4) of WISE to represent the star formation activity of the galaxies. The W3- and W4-based star formation rates are usually overestimated due to the star emission in low star-forming galaxies. Stellar continuum emission could contribute to MIR fluxes of elliptical galaxies with an average overestimation of ~ 13.95 and ~ 0.77% from the observed fluxes of WISE W3 and W4-bands, which determined by using the estimated WISE W3 and W4 flux correction factors. Better SFRs can be obtained by subtracting the stellar contribution of the sources. Our result highlights the possibility of the existence of unknown mechanisms triggering the continuous star formation activities in elliptical galaxies.